Radiological evaluation in living donor liver transplantation (LDLT): the effets of variations in segment 4 artery on the ratio of left lobe volume to total liver volume (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate whether the variations in the origin of the segment 4 artery effects the left liver lobe volume ratio to the total liver volume in living donor liver transplantation (LDLT).